2018
DOI: 10.1111/echo.14032
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional transthoracic echocardiographic identification of individual cusps of the pulmonary valve: Potential misidentification by the two‐dimensional technique

Abstract: We demonstrate the incremental value of live/real time three-dimensional transthoracic echocardiography (3DTTE) over the two-dimensional modality in the identification of all three cusps of the pulmonary valve in patients in whom only two leaflets could be detected by the latter technique. This was because of the ability of 3DTTE to view the cusps enface permitting assessment of relationship to one another and the surrounding cardiac structures. In addition, 3DTTE showed not only the potential errors that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Two‐dimensional TTE is the conventional first step and is well known as a cost‐effective diagnostic tool for heart valve evaluation. However, PV morphology is challenging for conventional 2D echo because of the anatomic localization of the PV under the sternum, and the basic physics of ultrasound penetration through the chest wall and pulmonary parenchyma 3,13,18,21,25,28,29 . Typically, only two cusps of the PV can be visualized simultaneously by 2D TTE even while utilizing short‐axis views.…”
Section: D Transthoracic Echocardiography In Pv Imagingmentioning
confidence: 99%
See 4 more Smart Citations
“…Two‐dimensional TTE is the conventional first step and is well known as a cost‐effective diagnostic tool for heart valve evaluation. However, PV morphology is challenging for conventional 2D echo because of the anatomic localization of the PV under the sternum, and the basic physics of ultrasound penetration through the chest wall and pulmonary parenchyma 3,13,18,21,25,28,29 . Typically, only two cusps of the PV can be visualized simultaneously by 2D TTE even while utilizing short‐axis views.…”
Section: D Transthoracic Echocardiography In Pv Imagingmentioning
confidence: 99%
“…The 3D TTE en face view allows concurrent visualization of all three PV leaflets, as well as assessments of the RVOT and main pulmonary artery, with additional improved quantitative assessment of pulmonary valve stenosis and regurgitation. 2,5,14,21,24,26–28,30,31 One recent study showed that 3D TTE was capable of visualization of all three leaflets image in all study subjects successfully, while 2D TTE only can image one or two leaflets partially 25 . Kelly et al showed PV morphological features are discerned accurately in 60% of patients, and this percentage can increase to 77% when patients with poor image quality on 2D TTE are excluded 17 .…”
Section: D Transthoracic Echocardiography In Pv Imagingmentioning
confidence: 99%
See 3 more Smart Citations